High-performance modified epoxy boron phenolic aldehyde anti-corrosion composite coating, composite coating and preparation method of high-performance modified epoxy boron phenolic aldehyde anti-corrosion composite coating

By using boron-modified phenolic resin and end-hydroxy-terminated boric acid-based polyethersulfone in bisphenol A-type epoxy resin, a semi-interpenetrating network structure is formed, and the problem of degradation of corrosion resistance of epoxy resin coating in high-temperature environments is solved. , significantly improves the heat resistance and toughness of the coating, and is suitable for a variety of working environments.

CN119192957APending Publication Date: 2024-12-27JILIN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411556473.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Bisphenol A type epoxy resin has deteriorated corrosion resistance, insufficient high temperature resistance and high brittleness during long-term use, resulting in the coating being easily corroded in high temperature environments.

Method used

Boron-modified phenolic resin is used as the curing agent, and terminal hydroxyl-terminated boric acid-based polyethersulfone is introduced as the modifier. The heat resistance and toughness of the coating are enhanced through boron-oxygen bonds and hydrogen bonds to form a semi-interpenetrating network structure.

Benefits of technology

It significantly improves the heat resistance, toughness and thermal stability of the coating, extends corrosion resistance, enhances corrosion resistance to metal substrates, and is suitable for a variety of working environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192957A_ABST
    Figure CN119192957A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance modified epoxy boron phenolic aldehyde anti-corrosion composite coating, a composite coating and a preparation method thereof, and belongs to the technical field of coatings. The composite coating is composed of bisphenol A type epoxy resin, a boron modified phenolic resin curing agent, a hydroxyl-terminated boric acid-based polyether sulfone modifier, a pigment filler and a diluent. Boron modified phenolic resin is selected as a bisphenol A phenolic resin curing agent, and after curing and crosslinking, the heat resistance of a coating is greatly improved; according to the present invention, the hydroxyl-terminated boric acid-based polyether sulfone is adopted as the modifier, the existence of the hydroxyl-terminated boric acid-based polyether sulfone can improve the overall heat resistance of the coating through the interaction with the hydrogen bond on the polymer chain, and the B-OH bond contained in the molecular structure of the hydroxyl-terminated boric acid-based polyether sulfone resin participates in the epoxy group reaction during the curing process; the crosslinking density of the coating is further increased. The composite coating provided by the invention greatly slows down the corrosion rate of a metal matrix in practical application, and has huge application potential in the field of anticorrosive coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a high-performance modified epoxy boron phenolic anti-corrosion composite coating, a composite coating and a preparation method thereof. Background Art

[0002] Metal corrosion and antifouling can cause significant direct and indirect economic losses. Direct losses are mainly due to the repair and replacement of deteriorated materials, the use of more corrosion-resistant materials, and the use of expensive coatings and inhibitors; indirect losses include reduced efficiency, production stoppages and product waste, overdesign and pollution. According to a study, the total direct cost of anti-corrosion technology in the United States each year accounts for 3.1% of the US GDP. It is estimated that the cost of solving the global corrosion problem is about 3.4% of the global GDP. According to a study by the Chinese Academy of Engineering, China's annual corrosion cost is about 310 billion US dollars, accounting for 3.34% of China's GDP.

[0003] Paint is a common material composed of film-forming substances, pigments, fillers, solvents and additives, which can be used for protection, decoration, marking and other special functions. Anti-corrosion coating protection refers to the coating of a layer of anti-corrosion coating with shielding and isolation functions on the protected metal material to isolate the corrosive medium and prevent or delay its contact with the metal substrate. Anti-corrosion coatings include inorganic anti-corrosion coatings and organic anti-corrosion coatings. Among them, organic anti-corrosion coatings are widely used in the field of metal corrosion protection due to their low cost, strong processability, strong functionality and simple construction conditions.

[0004] Epoxy resin is an important engineering material with the characteristics of high strength, wear resistance, corrosion resistance, and good insulation performance. Therefore, it is widely used in aerospace, automobile, electronics, construction, and shipbuilding. It can be used as coatings, adhesives, composite materials, electronic packaging materials, etc. Epoxy resin is an excellent anti-corrosion matrix resin. Epoxy coatings are widely used due to their high adhesion to metals and excellent water and chemical resistance. The large number of stable chemical bonds in epoxy resins give it high chemical stability. The general structural formula of bisphenol A epoxy resin is shown in (1). Bisphenol A epoxy resin is the most produced and representative of all epoxy resins. It is usually prepared by substitution reaction of epichlorohydrin and bisphenol A resin. The reaction usually requires the addition of an alkaline catalyst to catalyze the reaction. The resin can have different repeating units and molecular weights. The type of repeating units and the content of epoxy groups in the resin determine the performance of the resin. When the molecular weight is low, the resin behaves as a low-viscosity liquid at room temperature, while when the molecular weight is increased to a certain level, the resin behaves as a high-viscosity liquid or a block solid.

[0005]

[0006] Polyethersulfone is a special engineering plastic. The rigid groups and flexible groups in its molecular structure give it excellent flexibility, impact resistance, heat resistance and hardness. In addition, polyethersulfone has excellent metal adhesion and is expected to be used as a filler in epoxy resin to prepare composite coatings to improve the long-term corrosion resistance of epoxy resin. The structural formula of polyethersulfone is shown in (2). Polyethersulfone has good adhesion, mechanical properties and heat resistance. It also has excellent aging resistance and chemical stability. It can be used for 20 years at 180°C and is applicable to many chemicals. At present, polyethersulfone has been widely used in many fields such as electronics, machinery, medical equipment, water heaters, etc. At the same time, due to its excellent metal adhesion and corrosion resistance, polyethersulfone has gradually been recognized by the coating field.

[0007]

[0008] The Chinese invention patent "Method for Modification of Synergistic Toughening of Epoxy Resins (CN 116285228 A)" simultaneously introduces liquid rubber with terminal groups and polyethersulfone into the epoxy resin matrix to generate differential spherical phase structures and semi-interpenetrating polyethersulfone structures, effectively realizing the bonding between the filler and the matrix, thereby achieving the toughening effect on the matrix and greatly improving the impact toughness of the epoxy resin.

[0009] The Chinese invention patent "A method for preparing a marine anti-corrosion composite coating (CN 110041807 A)" adds a mixed slurry of organosilicon-modified bisphenol A novolac epoxy resin and polyethersulfone to a modified nano zinc oxide slurry to prepare a marine anti-corrosion composite coating.

[0010] The Chinese invention patent "Low-temperature-cured polyethersulfone coating composition, preparation method and coating process thereof (CN106905841A)" prepares a low-temperature-cured polyethersulfone coating from polyether sulfone resin, epoxy resin, polytetrafluoroethylene, curing agent, and diluent through high-speed stirring, aging, and substrate pretreatment, and elaborates on the coating process in detail.

[0011] Bisphenol A epoxy resin itself has three obvious disadvantages:

[0012] 1. Poor long-term anti-corrosion performance. Epoxy resin shows good anti-corrosion ability in the initial stage, but as time goes on, due to structural damage of the coating and long-term exposure to corrosive electrolyte, the anti-corrosion ability of the coating is seriously reduced.

[0013] 2. Epoxy resin cannot withstand high temperatures. Under high temperatures, the overall mechanical properties and strength of epoxy resin will decrease. Under high temperatures, defects will appear inside the coating, and corrosive media will more easily enter the coating and corrode the metal substrate.

[0014] 3. The cured product is brittle and has poor impact resistance. Usually, an elastomer is added to enhance toughness.

[0015] Boron phenolic resin is a new type of resin with a three-dimensional network structure containing boron atoms formed after the reaction by introducing boron elements into the molecular structure of phenolic resin through chemical reaction. Boron phenolic resin has good physical and chemical stability and excellent acid resistance. Compared with ordinary phenolic resin, the bond energy of BO in boron phenolic resin is 774.04 kJ / mol, which is more than twice the bond energy of CC in ordinary phenolic resin, that is, its thermal stability is stronger than that of ordinary phenolic resin. And the BO bond has flexibility, which improves the disadvantage of large brittleness of ordinary phenolic resin. The rigid group and flexible group contained in the molecular structure of polyethersulfone give it excellent flexibility, impact resistance, heat resistance and hardness. In order to further improve the long-term corrosion resistance and thermal stability of the coating, a hydroxyl-terminated boric acid polyethersulfone was synthesized as a modifier. The synthesized hydroxyl-terminated boric acid polyethersulfone resin was added to the coating composition as a modifier, and the hydroxyl-terminated boric acid polyethersulfone had good compatibility and a very stable homogeneous phase in the epoxy resin coating. Summary of the invention

[0016] The purpose of the present invention is to provide a high-performance modified epoxy boron phenolic anti-corrosion composite paint, composite coating and a preparation method thereof.

[0017] The present invention selects a synthetic boron-modified phenolic resin as a bisphenol A phenolic resin curing agent, and after curing and crosslinking, the heat resistance of the coating is greatly improved. The terminal hydroxyl-terminated boric acid polyether sulfone is used as a modifier. The presence of the terminal hydroxyl group can improve the overall heat resistance of the coating by interacting with the hydrogen bonds on the polymer chain, and the B-OH bond contained in the molecular structure of the terminal hydroxyl-terminated boric acid polyether sulfone resin participates in the epoxy group reaction during the curing process, further increasing the crosslinking density of the coating. The composite coating provided by the present invention greatly slows down the corrosion rate of the metal substrate in practical applications, and has great application potential in the field of anti-corrosion coatings.

[0018] The reaction of phenolic hydroxyl group with epoxy group and B-OH group is shown in (3):

[0019]

[0020] During heat curing, high-energy boron-oxygen bonds are introduced between molecules. During heat curing, the boron-oxygen bonds are interconnected with the benzene rings, further improving the mechanical properties and heat resistance of the coating. In addition, due to the presence of the hydroxyl-terminated boric acid polyethersulfone, it forms a semi-interpenetrating network structure with the epoxy resin, which improves the overall toughness of the composite coating without affecting the heat resistance and thermal stability of the coating itself. This greatly improves the shortcomings of bisphenol A epoxy resin coatings, such as poor heat resistance, poor toughness, and high brittleness.

[0021] The high-performance modified epoxy boron phenolic anti-corrosion composite coating described in the present invention is calculated as 100% by mass fraction of each component, and the composite coating is composed of 30-35% of bisphenol A epoxy resin, 7-9% of boron-modified phenolic resin curing agent, 1-5% of terminal hydroxyl-terminated boric acid polyether sulfone modifier, 0-1% of pigment and filler, and 55-62% of diluent; the present invention uses the synthesized boron-modified phenolic resin as a curing agent for bisphenol A epoxy value, and the synthesized terminal hydroxyl-terminated boric acid polyether sulfone as a modifier, so that the coating has good thermal properties, and the bisphenol A epoxy resin and the terminal hydroxyl-terminated boric acid polyether sulfone have good overall compatibility. The coating as a whole has a very dense and stable homogeneous phase, and the microscopic morphology at the cross section is smooth and delicate. The prepared coating exhibits good stability, heat resistance, flexibility, acid resistance, and salt resistance, and is suitable for a variety of working environments, while still maintaining high-performance modified epoxy boron phenolic resin anti-corrosion coatings.

[0022] The structural formula of bisphenol A epoxy resin is shown in (1).

[0023]

[0024] n represents the degree of polymerization of bisphenol A epoxy resin, which is a linear resin; n>5, the number average molecular weight of bisphenol A epoxy resin is 6000-8000, and the epoxy equivalent is 2500-3300;

[0025] The preparation process of boron-modified phenolic resin is as follows:

[0026] In a four-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen outlet, phenol and toluenesulfonic acid as catalysts and toluene as a dehydrating agent are added respectively, and the temperature is raised to 70-90°C and then boric acid is added, and then the temperature is kept at 90-110°C in a vacuum for 1.5-3.0 hours; then polyformaldehyde is added, and the temperature is raised to 130-150°C for condensation reaction for 2-5 hours; after the polyformaldehyde is completely dissolved, the distilled water is removed, and then the temperature is cooled to 20-30°C to obtain a boron-modified phenolic resin, whose structural formula is shown in (4):

[0027] The molar ratio of phenol to paraformaldehyde is 0.5:0.2-0.3, the molar amount of boric acid is 3-6% of the molar amount of phenol, and the molar amount of toluenesulfonic acid is 1-5% of the total molar amount of phenol, paraformaldehyde and boric acid; and the number average molecular weight of the obtained boron-modified phenolic resin is 400-800.

[0028]

[0029] q represents the degree of polymerization of the boron-modified phenolic resin, which is an integer of 2 to 10;

[0030] The preparation steps of the hydroxyl-terminated boric acid-based polyethersulfone modifier are as follows:

[0031] 1. Add phenolphthalein, 4,4'-dichlorodiphenyl sulfone and N-methylpyrrolidone to a three-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, respectively, and stir at a constant temperature of 60-80°C for 0.5-2h under the action of nitrogen. After the raw materials are fully dissolved, add potassium carbonate as a salt-forming agent and toluene as a water-carrying agent, heat to 140-160°C and stir for 2-5h. After obvious stratification is observed, remove the water-carrying agent, and then heat to 170-190°C and stir for 3-6h;

[0032] The molar ratio of phenolphthalein to 4,4'-dichlorodiphenyl sulfone is 1.1-1.2:1; toluene should be excessive in the reaction, the amount of N-methylpyrrolidone added should be sufficient to dissolve the reactants, and the molar ratio of potassium carbonate to phenolphthalein is 0.1-0.15:0.1.

[0033] 2. Cool the product of step 1 to 70-90°C, then add N,N-dimethylacetamide and glacial acetic acid to dilute so that the product of step 1 is evenly dispersed; then add diacyl chloride (the molar ratio of the product of step 1 to diacyl chloride is 5:1.8-2.2) and stir for 10-15h, add 3-aminophenylboric acid (the molar ratio of the product of step 1 to 3-aminophenylboric acid is 5:0.7-1.5) and stir for 20-30h; finally, precipitate in a mixed solvent of ethanol and water in a volume ratio of 2-4:1 for 10-15h, filter, wash and dry the product to obtain a hydroxyl-terminated boric acid-based polyethersulfone modifier, the structural formula of which is shown in Figure (5):

[0034]

[0035] m represents the polymerization degree of the hydroxyl-terminated boric acid polyether sulfone, which is 20 to 100; the intrinsic viscosity of the hydroxyl-terminated boric acid polyether sulfone modifier is 0.30 to 0.42.

[0036] The preparation method of the high-performance modified epoxy boron phenolic anti-corrosion composite coating of the present invention is as follows:

[0037] Dissolve bisphenol A epoxy resin in a diluent at a stirring speed of 1000-2000 r / min, wherein the mass fraction of bisphenol A epoxy resin in the diluent is 30-40%, then increase the speed to 3500-4000 r / min, add hydroxyl-terminated boric acid-based polyethersulfone and pigment filler respectively, stir for 3-6 hours, add boron-modified phenolic resin curing agent, stir for 15-30 minutes, and then stand and mature for 0.5-2.0 hours to obtain the epoxy phenolic high-performance anti-corrosion composite coating;

[0038] The pigment and filler is one of graphite or titanium dioxide;

[0039] The diluent consists of N,N-dimethylacetamide, cyclohexanone and propylene glycol methyl ether acetate in a mass ratio of 4:2:1.

[0040] The preparation method of the high performance modified boron phenolic epoxy anti-corrosion composite coating is as follows:

[0041] A diluent is added to the epoxy phenolic high-performance anti-corrosion composite coating to adjust the viscosity (apply four cups for 60 to 90 seconds), and then the composite coating with adjusted viscosity is sprayed onto a metal substrate that has been sandblasted, cleaned with ethanol and acetone, and dried using an air spray gun and an air compressor. The coating surface is dried at 40 to 60° C., and then cured at 90 to 110° C. for 0.5 to 2.0 h, 140 to 160° C. for 0.5 to 2.0 h, and 190 to 210° C. for 0.3 to 0.8 h, thereby obtaining a composite coating with a thickness of 80 to 100 μm.

[0042] The present invention uses boron-modified phenolic resin as a curing agent and uses terminal hydroxyl-terminated boric acid-based polyethersulfone as a modifier to improve the problem of insufficient overall heat resistance of the original bisphenol A coating. The composite coating has a higher 5% thermal weight loss temperature (414° C.), indicating that the coating has good thermal stability. Long-term electrochemical impedance spectroscopy (EIS) measurement is performed in a 3.5wt% NaCl solution. 0.01Hz Up to 10 10 Ωcm 2 , compared with bisphenol A epoxy resin and boron modified phenolic resin varnish, its 60d|Z|f= 0.01Hz -2 orders of magnitude, the basic mechanical properties of epoxy phenolic high-performance anti-corrosion coatings are relatively outstanding, and the adhesion level reaches level 0. Generally speaking, the better the coating adhesion, the better its corrosion resistance ( Figure 5 ). The bending toughness of the coating is 1mm, which improves the shortcomings of the original epoxy phenolic coating varnish, which is brittle and has poor toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 : Infrared test result curve of boron-modified phenolic resin and hydroxyl-terminated boric acid-based polyethersulfone prepared in Example 1 and Example 2;

[0044] like Figure 1 As shown in the figure, 3225cm -1 , 3435cm -1 They are the -OH stretching vibration absorption peaks of boron-modified phenolic resin and hydroxyl-terminated boric acid-based polyethersulfone, 1386 cm -1 The BO stretching vibration peak appears at 1457 cm -1The benzene ring double bond vibration peak and the 1140cm-1S=O characteristic peak appear in the infrared curve of the terminal hydroxyl-terminated boric acid group, which can prove that the present invention successfully obtains the boron-modified phenolic resin and the terminal hydroxyl-terminated boric acid polyether sulfone.

[0045] Figure 2 : TGA curves of the composite coating prepared in Example 5 and the bisphenol A type epoxy resin and boron modified phenolic resin varnish coating prepared in Comparative Example 1;

[0046] like Figure 2 As shown, the 5% thermal weight loss temperature of the bisphenol A epoxy resin and boron-modified phenolic resin varnish coating prepared in Comparative Example 1 is 403°C; by introducing terminal hydroxyl-terminated boric acid polyether sulfone into the bisphenol A epoxy resin and boron-modified phenolic resin varnish coating, the 5% thermal weight loss temperature of the composite coating prepared in Example 5 is increased to 414°C.

[0047] Figure 3 : DSC curves of the composite coating prepared in Example 6 and the bisphenol A type epoxy resin and boron-modified phenolic resin varnish coating prepared in Comparative Example 1;

[0048] like Figure 3 As shown, the glass transition temperature of the bisphenol A epoxy resin and boron-modified phenolic resin varnish coating prepared in Comparative Example 1 is 110°C; by introducing the terminal hydroxyl-terminated boric acid polyether sulfone into the bisphenol A epoxy resin and boron-modified phenolic resin varnish coating, the glass transition temperature of the composite coating prepared in Example 6 is increased to 120°C, and the coating has only one glass transition temperature, which also proves that the terminal hydroxyl-terminated boric acid polyether sulfone has excellent compatibility in the bisphenol A epoxy resin boron-modified phenolic resin system.

[0049] Figure 4 :Example 7( Figure 4 (1)) and Comparative Example 1 ( Figure 4 (2)) Cross-sectional scanning electron micrograph of the coating prepared; it can be seen from the figure that comparative example 1 ( Figure 4 (2)) The bisphenol A epoxy resin and boron-modified phenolic resin varnish prepared has some defects inside, and some small holes are irregularly distributed throughout the coating, which affects the density of the coating to a certain extent. The corrosion resistance of the coating is greatly weakened in a long-term corrosive environment. Figure 4 (1)) The end-hydroxyl-terminated boric acid polyethersulfone was introduced into the bisphenol A epoxy resin and boron-modified phenolic resin varnish. There were no obvious defects inside the coating, no tiny holes around it, and the density of the coating was further improved. The roughness inside the coating increased, and no obvious phase separation was seen in the figure, ensuring that good corrosion resistance can be maintained in a long-term anti-corrosion environment.

[0050] Figure 5:From Example 7( Figure 5 (1)) and Comparative Example 1 ( Figure 5 (2)) Electrochemical impedance test diagram of the prepared composite coating (immersed in 3.5wt.% NaCl solution for 60 days); It can be seen from the figure that Comparative Example 1 ( Figure 5 (2)) In the initial stage of immersion, the coating of bisphenol A epoxy resin and boron-modified phenolic resin varnish has good shielding properties, 17d|Z|f= 0.01Hz Up to 10 10 Ωcm 2 However, as time goes by and the corrosive medium penetrates deeper, |Z|f= 0.01Hz There was a significant decline, and it dropped to 10 after 60 days. 8 By Example 7 ( Figure 4 (1) After introducing the hydroxyl-terminated boric acid-based polyethersulfone into the bisphenol A epoxy resin and boron-modified phenolic resin varnish, the coating was 0.01Hz Up to 10 10 Ωcm 2 The curve is almost straight line, and the slope is close to -1. The coating still has a high anti-corrosion shielding effect in 60d. DETAILED DESCRIPTION

[0051] Embodiment 1:

[0052] In a four-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, 47.06g (0.5mol) of phenol, 4.5g of toluenesulfonic acid as a catalyst, and 55mL of toluene as a dehydrating agent were added respectively, and 0.93g of boric acid was added after the temperature was raised to 80°C, and then 9.01g (0.2mol) of polyformaldehyde was added after the temperature was raised to 100°C in a vacuum and kept for 2h, and the temperature was raised to 140°C for condensation reaction for 3h; after dissolution, the distilled water was removed by stirring under reduced pressure, and cooled to 25°C to obtain 55.72g of boron-modified phenolic resin. The boron-modified phenolic resin was measured by a PL-GPC220 high-temperature gel permeation chromatograph to obtain a molecular weight Mn=470.

[0053] Embodiment 2:

[0054] In a three-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, 31.8 g (0.1 mol) of phenolphthalein, 14.46 g (0.12 mol) of 4,4'-dichlorodiphenyl sulfone and 145 mL of N-methylpyrrolidone were added respectively, and stirred at 70°C for 1 h under the action of nitrogen. After the solution was fully dissolved, 17.94 g (0.13 mol) of potassium carbonate as a salt-forming agent and 65 mL of toluene as a water-carrying agent were added, and the temperature was raised to 150°C and stirred for 4 h. After obvious stratification was observed, the water-carrying agent was removed, and the temperature was raised to 180°C and stirred for 4 h; then cooled to 85°C. 37.04g of the product was diluted with 1200mL of N,N-dimethylacetamide and 15g of glacial acetic acid, and then 3.4mL of diacyl chloride was added and stirred for 12h, and then 2.74g of 3-aminophenylboronic acid was added and stirred for 24h; then precipitated in a mixed solvent of anhydrous ethanol and water (volume ratio 3:1) for 12h, and the obtained product was first crushed with a tissue grinder, and then filtered repeatedly, washed with acetone, and dried in a vacuum oven at 60°C for 12h to obtain 39.13g of hydroxyl-terminated boric acid-based polyethersulfone modifier. The molecular weight of the polymer was measured using an Ubbelohde viscometer, and the intrinsic viscosity was 0.33.

[0055] Embodiment 3:

[0056] In a three-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, 31.8 g (0.1 mol) of phenolphthalein, 14.46 g (0.12 mol) of 4,4'-dichlorodiphenyl sulfone and 145 mL of N-methylpyrrolidone were added respectively, and stirred at 70 ° C for 1 h under the action of nitrogen. After the solution was fully dissolved, 17.94 g (0.13 mol) of potassium carbonate was added as a salt-forming agent and 65 mL of toluene as a water-carrying agent. The temperature was raised to 150 ° C and stirred for 5 h (with the increase of reaction time, the molecular weight and viscosity of the product increased). When stratification was observed, After obvious removal of water-carrying agent, the temperature was raised to 180℃ and stirred for 4h; cooled to 85℃, 37.86g of the obtained product was added to 1200mL of N,N-dimethylacetamide and 15g of glacial acetic acid for dilution, and then 3.4mL of diacyl chloride was added and stirred for 12h, and then 2.74g of 3-aminophenylboronic acid was added and stirred for 24h; then precipitated in a mixed solvent of anhydrous ethanol and water (volume ratio 3:1) for 12h, the obtained product was first crushed with a tissue grinder, then filtered repeatedly, washed with acetone, and dried in a vacuum oven at 60℃ for 12h to obtain 39.63g of hydroxyl-terminated boric acid-based polyethersulfone modifier. The molecular weight of the polymer was measured using an Ubbelohde viscometer, and the intrinsic viscosity was 0.40.

[0057] Embodiment 4:

[0058] At a stirring speed of 1500r / min, 24g of bisphenol A epoxy resin was added to a diluent consisting of 24g of N,N-dimethylacetamide, 12g of cyclohexanone, and 6g of propylene glycol methyl ether acetate, the speed was increased to 3500r / min, 1.2g of hydroxyl-terminated boric acid polyethersulfone and 0.24g of graphite were added and stirred for 3 hours, and then 6.0g of boron-modified phenolic resin was added, stirred for 0.5 hours, and then allowed to stand and mature for 0.5 hours to obtain 78g of epoxy phenolic high-performance anti-corrosion composite coating. The composite coating consists of 32.7% by mass of bisphenol A epoxy resin, 8.2% of boron-modified phenolic resin curing agent, 1.6% of hydroxyl-terminated boric acid polyethersulfone modifier, 0.3% of pigment and filler, and 57.2% of diluent.

[0059] After the sandblasted steel plate is cleaned with ethanol and acetone and dried, the paint viscosity is adjusted with a thinner using an air spray gun and an air compressor (apply four cups for 75 seconds) and then the paint is evenly sprayed on the steel plate. The paint surface is dried at 50°C, and then kept at 100°C for 1 hour, 150°C for 1 hour, and 200°C for 0.5 hours for curing, thereby obtaining a composite coating with a thickness of 90 to 100 μm.

[0060] Table 1: Coating performance data of Example 4

[0061]

[0062]

[0063] Embodiment 5:

[0064] At a stirring speed of 1500r / min, add 24g of bisphenol A epoxy resin to a composite diluent composed of 24g of N,N-dimethylacetamide, 12g of cyclohexanone, and 6g of propylene glycol methyl ether acetate, increase the speed to 3500r / min, add 2.4g of hydroxyl-terminated boric acid polyethersulfone and 0.24g of graphite and stir for 3 hours, then add 6.0g of boron-modified phenolic resin, stir for 0.5 hours, and then stand and mature for 0.5 hours to obtain 78.3g of epoxy phenolic high-performance anti-corrosion composite coating. The composite coating consists of 32.2% by mass of bisphenol A epoxy resin, 8.0% of boron-modified phenolic resin curing agent, 3.2% of hydroxyl-terminated boric acid polyethersulfone modifier, 0.3% of pigment and filler, and 56.3% of diluent;

[0065] After the sandblasted steel plate is cleaned with ethanol and acetone and dried, the paint viscosity is adjusted with a thinner using an air spray gun and an air compressor (apply four cups for 75 seconds) and then the paint is evenly sprayed on the steel plate. The paint surface is dried at 50°C, and then kept at 100°C for 1 hour, 150°C for 1 hour, and 200°C for 0.5 hours for curing, thereby obtaining a composite coating with a thickness of 90 to 100 μm.

[0066] Table 2: Coating performance data of Example 5

[0067]

[0068] Embodiment 6:

[0069] At a stirring speed of 1500r / min, add 24g of bisphenol A epoxy resin to a composite diluent composed of 24g N,N-dimethylacetamide, 12g of cyclohexanone, and 6g of propylene glycol methyl ether acetate, increase the speed to 3500r / min, add 3.6g of hydroxyl-terminated boric acid polyethersulfone and 0.24g of graphite and stir for 3 hours, then add 6.0g of boron-modified phenolic resin, stir for 0.5 hours and then stand for aging for 0.5 hours to obtain 78.7g of epoxy phenolic high-performance anti-corrosion composite coating. The composite coating consists of 31.7% by mass of bisphenol A epoxy resin, 7.9% of boron-modified phenolic resin curing agent, 4.7% of hydroxyl-terminated boric acid polyethersulfone modifier, 0.3% of pigment and filler, and 55.4% of diluent;

[0070] After the sandblasted steel plate is cleaned with ethanol and acetone and dried, the paint viscosity is adjusted with a thinner using an air spray gun and an air compressor (apply four cups for 75 seconds) and then the paint is evenly sprayed on the steel plate. The paint surface is dried at 50°C, and then kept at 100°C for 1 hour, 150°C for 1 hour, and 200°C for 0.5 hours for curing, thereby obtaining a composite coating with a thickness of 90 to 100 μm.

[0071] Table 3: Coating performance data of Example 6

[0072]

[0073] Embodiment 7:

[0074] At a stirring speed of 1500r / min, 24g of bisphenol A epoxy resin was added to a composite diluent consisting of 24g of N,N-dimethylacetamide, 12g of cyclohexanone, and 6g of propylene glycol methyl ether acetate, the speed was increased to 3500r / min, 4.8g of terminal hydroxyl-terminated boric acid polyethersulfone and 0.01g of graphite were added and stirred for 3 hours, then 6.0g of boron-modified phenolic resin was added, stirred for 0.5 hour, and then allowed to stand and mature for 0.5 hour to obtain 79g of epoxy phenolic high-performance anti-corrosion composite coating.

[0075] After the sandblasted steel plate is cleaned with ethanol and acetone and dried, the paint viscosity is adjusted with a thinner using an air spray gun and an air compressor (apply four cups for 75 seconds) and then the paint is evenly sprayed on the steel plate. The paint surface is dried at 50°C, and then kept at 100°C for 1 hour, 150°C for 1 hour, and 200°C for 0.5 hours for curing, thereby obtaining a composite coating with a thickness of 90 to 100 μm.

[0076] Table 4: Coating performance data of Example 7

[0077]

[0078] Comparative Example 1: Preparation of bisphenol A epoxy resin and boron-modified phenolic resin varnish coating

[0079] At a stirring speed of 1500r / min, 24g of bisphenol A epoxy resin was added to a composite diluent consisting of 24g of N,N-dimethylacetamide, 12g of cyclohexanone, and 6g of propylene glycol methyl ether acetate, and the speed was increased to 3500r / min. After stirring for 3 hours, 6.0g of boron-modified phenolic resin was added. After stirring for 0.5 hour, the mixture was allowed to stand and mature for 0.5 hour to obtain 77.2g of bisphenol A epoxy resin and boron-modified phenolic resin varnish coating.

[0080] After the sandblasted steel plate is cleaned with ethanol and acetone and dried, the paint viscosity is adjusted with a thinner using an air spray gun and an air compressor (apply four cups for 75 seconds) and then the paint is evenly sprayed on the steel plate. The paint surface is dried at 50°C, and then kept at 100°C for 1 hour, 150°C for 1 hour, and 200°C for 0.5 hours for curing, thereby obtaining a composite coating with a thickness of 90 to 100 μm.

[0081] Table 5: Comparative Example 1 coating performance data

[0082]

[0083] Through the results of various embodiments and comparative example 1, we can find that bisphenol A epoxy resin and boron-modified phenolic resin varnish have high adhesion, good hardness, and short-term corrosion resistance. However, the overall toughness grade of the varnish coating is not high, showing a certain brittleness, and the corrosion resistance is weakened to a certain extent in long-term corrosion protection. We successfully synthesized hydroxyl-terminated boric acid polyether sulfone as a modifier for bisphenol A epoxy resin and boron-modified phenolic resin varnish. It can be seen from the results that when hydroxyl-terminated boric acid polyether sulfone is introduced, the coating Tg (glass transition temperature) and 5% thermal weight loss temperature are further improved, and the heat resistance and thermal stability of the coating are enhanced. The bending toughness is increased from 4mm to 1mm, which greatly improves the toughness of the overall coating, and further solves the overall brittleness of the bisphenol A epoxy resin and boron-modified phenolic resin varnish coating. In addition, the introduction of hydroxyl-terminated boric acid polyethersulfone fills the defects caused by solvent volatilization during the curing process, further improves the overall density of the coating, and enables the coating as a whole to maintain a good corrosion-resistant shielding effect in a long-term corrosive environment.

Claims

1. A method for preparing a high-performance modified epoxy boron phenolic anti-corrosion composite coating, the steps of which are as follows: (1) Preparation of boron-modified phenolic resin In a four-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, phenol and toluenesulfonic acid as catalysts and toluene as a dehydrating agent are added respectively, and the temperature is raised to 70-90°C and then boric acid is added, and then the temperature is kept at 90-110°C in a vacuum for 1.5-3.0 hours; then polyformaldehyde is added, and the temperature is raised to 130-150°C for condensation reaction for 2-5 hours; after the polyformaldehyde is completely dissolved, the distilled water is removed, and then the flask is cooled to 20-30°C to obtain a boron-modified phenolic resin with a number average molecular weight of 400-800, whose structural formula is shown in (4). q is 2 to 10, indicating the degree of polymerization of the boron-modified phenolic resin; (2) Preparation of hydroxyl-terminated boric acid polyethersulfone modifier S1. Add phenolphthalein, 4,4'-dichlorodiphenyl sulfone and N-methylpyrrolidone to a three-necked flask equipped with a reflux device, a stirring device, a water separator, a thermometer and a nitrogen port, respectively, and stir at a constant temperature of 60-80°C for 0.5-2h under the action of nitrogen. After the raw materials are fully dissolved, add potassium carbonate as a salt-forming agent and toluene as a water-carrying agent, raise the temperature to 140-160°C and stir for 2-5h. After obvious stratification is observed, remove the water-carrying agent, and then raise the temperature to 170-190°C and stir for 3-6h; S2, cooling the product of step S1 to 70-90°C, then adding N,N-dimethylacetamide and glacial acetic acid to dilute so that the product of step S1 is evenly dispersed; then adding diacyl chloride and stirring for 10-15h, adding 3-aminophenylboric acid and stirring for 20-30h; finally, precipitating in a mixed solvent of ethanol and water in a volume ratio of 2-4:1 for 10-15h, filtering, washing and drying the product to obtain a hydroxyl-terminated boric acid-based polyethersulfone modifier with an intrinsic viscosity of 0.30-0.42, the structural formula of which is shown in Figure (5), m is 20 to 100, indicating the degree of polymerization of the hydroxyl-terminated boric acid polyethersulfone; (3) Preparation method of high performance modified epoxy boron phenolic anti-corrosion composite coating At a stirring speed of 1000-2000 r / min, bisphenol A epoxy resin is dissolved in a diluent, so that the mass fraction of bisphenol A epoxy resin in the diluent is 30-40%; then the speed is increased to 3500-4000 r / min, a hydroxyl-terminated boric acid-based polyethersulfone modifier and pigments and fillers are added respectively, and after stirring for 3-6 hours, a boron-modified phenolic resin curing agent is added, and after stirring for 15-30 minutes, the curing agent is allowed to stand for 0.5-2.0 hours to obtain the epoxy phenolic high-performance anti-corrosion composite coating; the sum of the mass fractions of each component is calculated as 100%, and the composite coating consists of 30-35% of bisphenol A epoxy resin by mass, 7-9% of boron-modified phenolic resin curing agent, 1-5% of hydroxyl-terminated boric acid-based polyethersulfone modifier, 0-1% of pigments and fillers, and 55-62% of diluent.

2. The method for preparing a high-performance modified epoxy boron phenolic anti-corrosion composite coating as claimed in claim 1, characterized in that: In step (1), the molar ratio of phenol to paraformaldehyde is 0.5:0.2-0.3, the molar amount of boric acid is 3-6% of the molar amount of phenol, and the molar amount of toluenesulfonic acid is 1-5% of the total molar amount of phenol, paraformaldehyde and boric acid.

3. The method for preparing a high-performance modified epoxy boron phenolic anti-corrosion composite coating as claimed in claim 1, characterized in that: In step (2), the molar ratio of phenolphthalein to 4,4'-dichlorodiphenyl sulfone is 1.1-1.2:1; toluene should be excessive in the reaction, the amount of N-methylpyrrolidone added should be sufficient to dissolve the reactants, and the molar ratio of potassium carbonate to phenolphthalein is 0.1-0.15:0.

1.

4. The method for preparing a high-performance modified epoxy boron phenolic anti-corrosion composite coating as claimed in claim 1, characterized in that: In step (2), the molar ratio of the product of step S1 to the diacyl chloride is 5:1.8-2.2, and the molar ratio of the product of step S1 to 3-aminophenylboronic acid is 5:0.7-1.

5.

5. The method for preparing a high-performance modified epoxy boron phenolic anti-corrosion composite coating as claimed in claim 1, characterized in that: The pigment filler in step (2) is one of graphite or titanium dioxide; the diluent is composed of N,N-dimethylacetamide, cyclohexanone and propylene glycol methyl ether acetate in a mass ratio of 4:2:

1.

6. A high-performance modified epoxy boron phenolic anti-corrosion composite coating, characterized in that: The method is prepared by any one of claims 1 to 5.

7. A method for preparing a high-performance modified boron phenolic epoxy anti-corrosion composite coating, characterized in that: A diluent is added to the high-performance modified epoxy phenolic high-performance anti-corrosion composite coating as described in claim 6 to adjust the viscosity, and then the composite coating after viscosity adjustment is sprayed onto a metal substrate, the coating surface is dried at 40-60°C, and then the coating is kept at 90-110°C for 0.5-2.0h, 140-160°C for 0.5-2.0h, and 190-210°C for 0.3-0.8h for curing, thereby obtaining a high-performance modified boron phenolic epoxy anti-corrosion composite coating with a thickness of 80-100μm.

8. The method for preparing a high-performance modified boron phenolic epoxy anti-corrosion composite coating according to claim 7, characterized in that: The viscosity after adjustment with diluent is 60 to 90 seconds for coating four cups.

9. The method for preparing a high-performance modified boron phenolic epoxy anti-corrosion composite coating according to claim 7, characterized in that: The composite coating after viscosity adjustment is sprayed onto the metal substrate which has been sandblasted, cleaned with ethanol and acetone, and dried.

10. A high performance modified boron phenolic epoxy anti-corrosion composite coating, characterized in that: The method is prepared by any one of claims 7 to 9.

Citation Information

Patent Citations

  • Low-temperature curing polyether sulfone coating composition and preparation method thereof, as well as coating process

    CN106905841A

  • Preparation method for marine anticorrosive composite coating

    CN110041807A

  • Modification method for synergistic toughening of epoxy resin

    CN116285228A

  • Amido bond phenylboronic acid ester-containing polyether sulphone polymer and preparation method thereof

    CN103242530A

  • Preparation method of anticorrosive coating

    CN107118652A